Challenges in tin perovskite solar cells. Issue 41 (17th September 2021) - Aldamasy, Mahmoud; Iqbal, Zafar; Li, Guixiang; Pascual, Jorge; Alharthi, Fahad; Abate, Antonio; Li, Meng
Abstract : Perovskite solar cells are the rising star of third-generation photovoltaic technology. Abstract : Perovskite solar cells are the rising star of third-generation photovoltaic technology. With a power conversion efficiency of 25.5%, the record efficiency is close to the theoretical maximum efficiency of a single-junction solar cell. However, lead toxicity threatens commercialization efforts and market accessibility. In this context, Sn-based perovskites are a safe alternative. Nevertheless, the efficiency of Sn-based devices falls far behind the efficiency of Pb-based counterparts. This concise review sheds light on the challenges that the field faces toward making Sn-based perovskites the perovskite photovoltaic benchmark. We identified four key challenges: materials and solvents, film formation, Sn(ii ) oxidation, and energy band alignment. We illustrate every single challenge and highlight the most successful attempts to overcome them. Finally, we provide our opinion on the most promising trends of this field in the future.